1998
DOI: 10.1577/1548-8675(1998)018<0886:rahapc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relations among Habitat and Population Characteristics of Spotted Bass in Kansas Streams

Abstract: Spotted bass Micropterus punctulatus are popular sport fish in streams and reservoirs throughout the southeastern United States. Despite their popularity, there is a paucity of information on population characteristics and habitat requirements of spotted bass in streams. The purpose of this study was to document the factors that influence spotted bass populations in Kansas streams. Study sites were selected throughout the native range of spotted bass in Kansas. Spotted bass were sampled by electrofishing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Near‐bank habitat used by Spotted Bass may have provided velocity refuge and cover for ambushing prey (Harris et al, 2018). Woody structures are used by Spotted Bass across small and large river systems (Goclowski et al, 2013; Lobb & Orth, 1991; Scott & Angermeier, 1998; Tillma, Guy, & Mammoliti, 1998), and our results suggest cover is also important during all seasons.…”
Section: Discussionsupporting
confidence: 55%
“…Near‐bank habitat used by Spotted Bass may have provided velocity refuge and cover for ambushing prey (Harris et al, 2018). Woody structures are used by Spotted Bass across small and large river systems (Goclowski et al, 2013; Lobb & Orth, 1991; Scott & Angermeier, 1998; Tillma, Guy, & Mammoliti, 1998), and our results suggest cover is also important during all seasons.…”
Section: Discussionsupporting
confidence: 55%
“…For example, woody debris may function as a source of invertebrate prey during early ontogeny and as structure (e.g., ambush areas) for adults. Tillma et al (1998) found that the area of root wad and undercut bank habitat explained over 60% of the variation in the relative abundance and biomass of spotted bass M. punctulatus in Kansas streams. The authors suggested that woody debris was important because it often formed the only source of structural diversity in their study streams.…”
Section: Discussionmentioning
confidence: 99%
“…See Tillma et al (1998) for a detailed description of sampling methods and sample sites. Sampled fish were measured to the nearest mm total length (TL), and scales were collected below the lateral line near the tip of the pectoral fin for age determination and growth analysis (DeVries and Frie 1996) Scale impressions were made on acetate slides and aged using a microfiche projector.…”
Section: Methodsmentioning
confidence: 99%